Analysis of Canva Media Learning Al-Islam and Muhammadiyah at MTs Muhammadiyah Waru - Syukron, Hidayatul Layl Umi; Inayati, Nurul Latifatul (FKIP - Universitas Riau, 2025)
The use of learning media is currently very important to be used by teachers or lecturers in delivering material. This study aims to describe the implementation of Al-Islam and Muhammadiyah learning by utilizing Canva Media in MTs Muhammadiyah Waru and to describe the obstacles in the use of Canva Media in teaching Al-Islam and Muhammadiyah in MTs Muhammadiyah Waru. This type of research is carried out through a qualitative approach by means of observation, interviews, and documentation for data collection. Based on the conclusion of the results of this study, the use of Canva media when teaching Al-Islam and Kemuhammadiyahan can increase student participation, make the material easier to understand, and smooth the learning process to be more interactive and interesting. However, there are several challenges faced. These include limited access to technological devices, teachers' ability to manage Canva properly, and internet network issues. However, Canva's media as a whole helps with learning; Therefore, educators must be trained and given more technology facilities to support the use of digital media in the classroom.